2018
DOI: 10.1021/acs.jafc.8b03910
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Safety Assurance of Six Fungicides Applied on Postharvest Cabbages Stored in a Natural Environment

Abstract: Postharvest disease is a major factor in the limited shelf life of many fruits and vegetables, and it is often managed using fungicidal spraying or soaking. In this study, we first tested the efficiency of six common fungicides on postharvest head cabbage (Brassica oleracea var. capitata) against Botrytis cinerea. Afterward, the elimination abilities of these six fungicides on different layers of cabbage heads were examined, and the effects of the household processes on residue removal were evaluated. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, long-term use of the existing fungicides has led to the emergence of fungicide-resistant P. capsici , which has resulted in control failures [ 7 , 8 ]. In addition, there is considerable concern regarding the adverse effects that some chemical fungicides have on the environment and food safety [ 9 ]. Therefore, there is an urgent need to develop natural, safe, and effective antifungal substances for P. capsici control.…”
Section: Introductionmentioning
confidence: 99%
“…However, long-term use of the existing fungicides has led to the emergence of fungicide-resistant P. capsici , which has resulted in control failures [ 7 , 8 ]. In addition, there is considerable concern regarding the adverse effects that some chemical fungicides have on the environment and food safety [ 9 ]. Therefore, there is an urgent need to develop natural, safe, and effective antifungal substances for P. capsici control.…”
Section: Introductionmentioning
confidence: 99%
“…Stir-frying can keep the food aromas and flavors with a small amount of oil at high temperatures and keep the food material crisp and fresh. 42 The effect of blanching and stir-frying procedures on iprodione residues in green garlic and garlic shoot was studied. High residue reduction was observed for iprodione in green garlic and garlic shoots, with percentages of 81.20% and 98.33% for blanching and 77.78% and 95.43% for stir-frying, respectively (Fig.…”
Section: Blanching and Stir-fryingmentioning
confidence: 99%
“…Our results, like previous studies, demonstrated a high level of efficiency in removing pesticide residues. 42 Zhibo Huan et al concluded that fungicides with high Kow values showed higher reductions under stir-frying compared to fungicides with low Kow values. 43 They reported that the removal rate might be associated with Kow and solubility in water.…”
Section: Blanching and Stir-fryingmentioning
confidence: 99%
“…digitatum is the most economically important citrus disease, especially in subtropical and tropical production areas such as Argentina . Disease management has traditionally been based on chemical fungicide application, but lately, many strains resistant to imazalil (IMZ) or thiabendazole (TBZ), which are two of the main products used to control this infectious agent, have been isolated. B. cinerea is a really destructive plant pathogen responsible for the Botrytis bunch rot or gray mold, which mainly affects grapes and strawberries, causing great losses to the table grape and wine industry .…”
Section: Introductionmentioning
confidence: 99%